ROLE OF ACCOUNTANTS IN THE BRITISH NATIONALIZATION PROGRAM. - Murphy, Mary E. (The Accounting Review, 1952)
Abstract British accountants have made an important contribution to the Commonwealth, in recent years, as a result of the Labor Party's plan to nationalize 20% of the economy. This section included the Bank of England and seven major industries-civil aviation, cables and wireless, coal, electricity, gas, cotton and transportation. In each of the fields named, public corporations were set up to operate the enterprises concerned in the national interest. Parliament placed the entire responsibility for operation of the coal industry upon the National Coal Board with no reference to divisions or areas, but area boards were appointed in the gas and electricity industries and in the transport field a number of executives were appointed to serve as the Transport Commission's agents. Compensation was not on a uniform basis. For the Bank of England and Cables and Wireless PLC, for instance, it was established on the basis of net maintainable revenue; for railways, air transport and electricity it was set on stock exchange quotations at stated dates and for collieries, on a global amount fixed by a tribunal.